Comparative maternal outcomes of oral nifedipine and intravenous labetalol for severe hypertension during pregnancy: an open label randomized controlled trial - Sharma, Monika; Thakur, Sita; Singh, Kamal; Shekhar, Shashank (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hypertensive diseases are commonly seen during pregnancy and remain one of the leading causes of maternal morbidity and mortality. Mostly commonly preferred drugs by health care providers for treatment of severe hypertension during pregnancy are labetalol and hydralazine. However, they require proper storage, intravenous access, and adequately trained staff for usage. Oral nifedipine in contrast is easier to use and widely available. Objective of this study was to report the efficacy and safety of oral nifedipine as compared to intravenous labetalol for treatment of severe hypertension during pregnancy. Methods: It was an open label randomized controlled trial in which 100 women with severe hypertension during pregnancy were enrolled. They were randomized to receive either incremental doses of intravenous labetalol every 20 minutes (total 300 mg) or 10 mg oral nifedipine every 20 minutes (up to 50 mg) to lower the blood pressure to safer levels. Results: Women receiving oral nifedipine took significantly less time to achieve target blood pressure [(37.6±23.3) minutes (SD) as compared to those receiving intravenous labetalol (52.0 minutes±27.95 (SD)]. Women receiving nifedipine for treatment also required significantly lesser doses to control the blood pressure [mean dose 1.8±1.1 (SD) versus 2.6±1.2 (SD) p=0.006]. There were two failures in labetalol group and one failure in nifedipine group. No serious adverse events were reported in either group. Conclusions: Oral nifedipine is equally efficacious to I.V. labetalol for treatment of severe hypertension during pregnancy and is easier to use in low resource settings.